PSXVI-39 Responses of growth performance, physiological and blood parameter to long-term heat stress in beef calves. (7th December 2018) - Kim, W; Lee, J; Peng, D; Conejos, J; Jo, Y; Jo, J; Seo, J; Choe, W; Kim, J; Kim, T; Lee, H
Abstract: The objective of this study was to investigate the growth performance, physiological and blood parameter responses of beef calves during and after sudden exposure to heat stress condition, compared with calves in thermoneutral conditions. Data were collected from four Korean native calves (BW 136.9 ± 6.23 kg and age 169.6 ± 4.60 d), which were kept at four designated temperature humidity index (THI) levels based on ambient temperature and humidity: Threshold (22 to 24 °C, 60%; THI = 68 to 70), Mild (26 to 28 °C, 60%; THI = 74 to 76), Moderate (29 to 31 °C, 80%; THI = 81 to 83) and Severe (32 to 34 °C, 80%; THI = 88 to 90) stress level. Calves were subjected to ambient temperature (22 °C) for 7 days, after which chamber temperature and humidity were raised to each THI level for 21 days. The blood metabolites were analyzed using biochemical analyzer-TBA-40FR. Physiological parameters of heat stress were measured, including rectal temperature (RT), skin temperature (ST) and heart rate (HR) every three days. Feed and water intake were recorded daily (at 0900), and body weight measured once a week. The results showed that RT (p = 0.001), ST (p = 0.001) and HR (p = 0.001) were significantly increased in the severe stress level compared with the threshold but had no effect on growth performance. Glucose and GOT levels were increased after sudden exposure to heat stress condition; however, as the high temperature condition was maintained, glucose and GOT levels returned to a normal range after 14 days. We suggest that physiological parameters (RT, ST and HR) were important indicators of calves under heat stress. In addition, calves exposed to heat stress had physiological responses that regulated metabolites in the blood, to maintain homeostasis during the long-term heat stress.